An analysis of selected children's tales by the Grimm brothers using M.A.K. Halliday's systematic grammar - Suganob, Cassandra Remo (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2013)
Using halliday's transitivity system in systematic functional grammar as framework, this study analyzes how violence is reflected in selected children's tales by the Grimm brothers--"Cinderella" and "Hansel and Gretel". The application of transitivity in the shorth stories has brought out the lexical items and features of the processes, participants, and circumstances in a clause. These provided relevant linguistic evidence useful in the investigation of violence as manifested in language. Upon the examination of the clauses, it is revealed that there is a preponderance of material and verbal processes in both of the stories. Violence is mainly represented in language through commands to do difficult tasks, the abuse, injury, and verbal insults carried out by the perpetrators and received by the victims. The lexical items show the dominance of negative associations used to describe the wickedness of the doers of the violent acts as well as the poor state of the sufferers. This study demonstrates how language functions as a medium of representation; that is, how speakers account for their experience of what goes around and inside them. There are manifestations of violence seen in various process types used by the different characters to represents themselves and their relationship with others.
Thesis (B.A. in English Language)
Keywords: Systemic grammar; Functionalism (Linguistics); Children -- Books and reading